Inovasi Pelayanan Administrasi Kependudukan Online (PADUKO) oleh Dinas Kependudukan dan Pencatatan Sipil Kota Padang Panjang - Mona Melinda; Syamsurizaldi; Muhammad Ichsan Kabullah (Nakhoda: Jurnal Ilmu Pemerintahan, 2020)
Public demand for excellent service affects the government to make various innovations. In that sense, the Civil Registration Office in Padang Panjang City creates innovation in online civil services (PADUKO). PADUKO innovation consists of 19 kinds of civil services and succeed to achieve the highest score between agencies in the Municipality of Padang Panjang in 2019. In this article, we would like to explore PADUKO innovation by the Civil Registration Service Office. This research has used the theory of the attributes of innovation by Everett M Rogers which says that there are five attributes of innovation that can determine innovation acceptance, which consists of relative advantage, compatibility, complexity, trialability, and observability. The method in this research is descriptive qualitative method with data collection techniques by interview, documentation, and observation, while the selection informants technique by purposive sampling technique. The validity of the used triangulation. Based on this fieldwork, PADUKO innovation was successful and accepted by the public. Five attributes of innovation by Everett M. Rogers also presence on PADUKO innovation. This can be seen from the perceived benefits in the form of effectivity, efficiency of cost, and energy, and the acceptance of services with the needs of the public. However, some problems are still found, such as poor network, server, and application problems.